A Localized Surface Plasmon Resonance Sensing Method for Simultaneous Determination of Atenolol and Amiloride in Pharmaceutical Dosage Forms and Urine Samples - Marwa R. El-Zahry (Journal of Analytical Methods in Chemistry)
This contribution describes a simple, fast, and sensitive application of localized surface plasmon resonance effect of silver nanoparticles for simultaneous determination of antihypertensive drugs’ mixture atenolol and amiloride in both pharmaceutical dosage forms and in biological samples (urine). Silver nanoparticles were prepared by chemical reduction of silver nitrate using hydroxylamine HCL in an alkaline medium. Application of silver-hydroxylamine nanoparticles (SH NPs) provides many advantages including reproducibility, sensitivity, and cost effective way of analyte determination. Amiloride has four amino groups which act as attachment points on the surface of silver nanoparticles resulting in a synergistic effect on the absorption intensity of atenolol, leading to increase the sensitivity of the determination of both compounds. This method shows excellent advantages comparing with the previously reported methods, including accuracy, precision, and selectivity. The linear range of atenolol is 1 × 10−5–1 × 10−4 mol·L−1 and of amiloride is 1 × 10−6–1 × 10−5 mol·L−1. The limit of detection (LOD) values of atenolol and amiloride are 0.89 × 10−5 and 0.42 × 10−6 mol·L−1, respectively.